2019
DOI: 10.12691/ajnr-7-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Saudi Female Students towards the Phenomena of Bullying Behaviors during Nursing Education Program

Abstract: Bullying is a growing problem in nursing education from the academia area to the clinical setting that is under-reported and tolerated by nursing students. Aim: The main aim is to explain the phenomena of bullying behaviors among Saudi female students during their study in nursing education program. Design: The study utilized a cross-sectional quantitative descriptive design. Setting: It conducted in the College of Applied Medical Sciences (CAMS) at University of Hafr Al-Batin (UHB) in Saudi Arabia. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…We also found that an increase in attacks on academic achievement and direct negative behaviors increases perceived and acute stress among nursing students. This result is consistent with the ndings of depression, and post-traumatic stress [29], which directly affect the professional skills of nursing students and their patients' safety [15]. Abdelaziz and Abu-Snieneh (2022) found that student exposure to bullying and maltreatment was related to poor mental health and perceived stress among nursing students [3].…”
Section: Discussionsupporting
confidence: 82%
“…We also found that an increase in attacks on academic achievement and direct negative behaviors increases perceived and acute stress among nursing students. This result is consistent with the ndings of depression, and post-traumatic stress [29], which directly affect the professional skills of nursing students and their patients' safety [15]. Abdelaziz and Abu-Snieneh (2022) found that student exposure to bullying and maltreatment was related to poor mental health and perceived stress among nursing students [3].…”
Section: Discussionsupporting
confidence: 82%
“…This was followed by receiving unfair evaluations of their work and others underestimating the value of their academic work. Mohamed [ 24 ] stated that the most frequent bullying behaviors reported by Saudi female nursing students were verbal. These students were often threatened with poor evaluations and had their work belittled.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the least common bullying behaviors reported by nursing students were being physically assaulted and unfairly treated because of race, incapacities, or weaknesses. Similarly, Mohamed [ 24 ] found that the least reported bullying behaviors were being treated poorly based on disability, racially motivated bullying, and physical abuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations